Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper analyzes poverty in Bangladesh. The paper highlights that poverty in Bangladesh has many facets, including low income, inadequate calorie intake, poor health and educational attainment, and limited access to social services. The paper reviews the recent trends in social indicators. It discusses definitions and the measurement of poverty, and relates poverty to growth scenarios. Poverty alleviation programs are reviewed, and the government's strategies to reduce poverty are also highlighted.